Gelatin modified ultrathin silk fibroin films for enhanced proliferation of cells. (18th March 2015) - Yang, Luyuan; Yaseen, Mohammed; Zhao, Xiubo; Coffey, Paul; Pan, Fang; Wang, Yuming; Xu, Hai; Webster, John; Lu, Jian R
Abstract: Silk fibroin (SF) films were modified with gelatin (G) to explore if such SF/G films could enhance the surface biocompatibility of silk as cell growth biomaterials. Ultrathin films were coated from aqueous SF solutions pre-mixed with different amounts of G. It was found that the SF/G blended films after methanol treatment were highly stable in physiological conditions. The incorporation of G smoothed the surface morphology of the SF/G films formed. Surface-exposed RGD sequences were successfully identified on the SF/G films through specific recognition of an integrin-mimicking peptide (bearing the sequence of CWDDGWLC). Cell culture experiments with 3T3 fibroblasts demonstrated that SF/G films with 1.2–20% (w/w) G gave clear improvement in promoting cell attachment and proliferation over pure SF films. Films containing 10–20% (w/w) of G showed cell attachment and growth even superior to the pure G films. The differences as observed from this study suggest that due to the lack of mechanical strength associated with its high solubility, G could not work alone as a cell growth scaffold. The enhanced cellular responses from the blended SF/G films must result from improvement in film stability arising from SF and in cytocompatibility arising from G. The results thus indicate the potential of the SF/G blends in tissue engineering and biomedical engineering where physical and biological properties could be manipulated via mixing either as bulk biomaterials or for coating purposes.